Nutrient uptake and fertilizer-use efficiency of maize hybrids under conservation agriculture with nutrient expert based SSNM practices - Kumar, V.; Singh, A.K.; Jat, S.L.; Parihar, C.M.; Pooniya, V.; Sharma, S. (Annals of Agricultural Research, 2016)
A field experiment was conducted at New Delhi during kharif season of 2013 to study the effect of nutrient expert - decision support system based nutrient management on nutrient uptake and nutrient use efficiency of maize (Zea mays) genotypes under conservation agriculture. It is based on the principle of site specific nutrient management (SSNM) which gave higher dose of K and N while lower dose of P were estimated over recommended fertilization practices (RDF) in this study. The results of experiment revealed that the N, P and K content and total uptake (grain, stover) was significantly higher with SSNM which remained at par with 100% RDF. Amongst genotypes significantly higher N content and total uptake (grain, stover) were obtained by CMH-08-292. The total phosphorus and potassium uptake was increased significantly by PMH-1, PMH-3 and CMH08-292. For micro nutrients, significantly higher Fe uptake was obtained by 100 % RDF, while Zn and Cu uptake was obtained by SSNM. Amongst genotypes, total Fe and Zn uptake was higher in CMH-08-292, while total Cu uptake was found significantly higher by PMH-3 and CMH-08-292. Harvest index of N, P, K, Zn and Cu was significantly higher in SSNM. Significantly higher K, Zn and Cu harvest index was obtained with SSNM. Amongst genotypes, S-6217 increased significantly higher N, P, K, Zn and Cu harvest index, whereas Fe harvest index was highest in PMH-3 over rest of the genotypes. Significantly higher N, P, K apparent recovery, higher N and P physiological efficiency was obtained with SSNM, whereas K physiological efficiency was significantly highest in 50% RDF. Amongst genotypes, apparent recovery and physiological efficiency of N, P and K was highest in PMH-3.